The Effect of Electronic Payment Systems on Financial Performance of Microfinance Banks in Niger State - Sakanko, Musa Abdullahi; David, Joseph (Esensi: Jurnal Bisnis dan Manajemen, 2019)
This study employs the cross sectional survey research design and the descriptive and ordinary least square regressions to examine the impact of Electronic-Payment Systems on the financial performance of Microfinance Banks and Institutions in Niger state, Nigeria. The results of the analysis indicate the presence of e-payment systems  in the bank, which enjoys impressive acceptability, due to its ease of use and convenience. In addition, ATM facility, Internet payment options, e-payment cards, and mobile banking platforms shows a significant positive impact on the financial performance of COE-Minna microfinance bank. In essence, the improvement and review of e-payment platforms’ security, so as to attract more users, coupled with the reduction of charges associated with the use of the platforms as well as sensitization of potential users were recommended.